INTERPRETATION OF THE STUDY OF SPEECH STYLES IN UZBEK LINGUISTICS (Scientific journal of the Fergana State University, 2024)
The fact that the means in our language have different appearances, and a variety of synonyms, allows us to use these means in this way. This choice requires a certain stylistic limitation of linguistic units in the speech process. The necessity of selective use of linguistic units in a social environment and their scientific and practical analysis in linguistics created a new direction in stylistics - functional stylistics. In the modern development of Uzbek linguistics, the study of functional styles has become an extremely pressing issue from a sociolinguistic point of view. One of the main reasons for this is the significant changes in the structure of the vocabulary of the Uzbek language in the conditions of independence, the expansion of communicative possibilities in the process of various interactions of the language and its constant improvement.